The scientific evolution of social justice leadership in education: structural and longitudinal analysis of the existing knowledge base, 2003–2022 - Karakose, Turgut; Tülübaş, Tijen; Papadakis, Stamatios (Frontiers in Education, 2023)
This study aims to delineate the intellectual and conceptual architecture of social justice leadership (SJL) research in education by reviewing the strategic themes that emerged during its scientific evolution. The study combines bibliometric performance and science mapping analysis of 135 articles on "SJL in education" retrieved from the Scopus database. SciMAT software (version 1.1.04) was used for the study since it allows for sequential analysis. Our analysis comprised three periods: Period 1 (2003-2012), Period 2 (2013-2017), and Period 3 (2018-2022). Studies during the first period mostly centred around transformative leadership, social justice and equity themes, whilst the research focus during the second period moved towards the roles of principals in enabling justice. During the third period, the analysis revealed more variety in the themes addressed by scholars. Instructional leadership roles of principals and the outcomes of social justice leadership, such as equity and well-being for different groups vulnerable to injustices, were the most prominent themes addressed during the last period. The study's findings enable us to reflect on this research field's well- or underdeveloped aspects. They would help guide research interest into the under-investigated or emerging themes of SJL, which would eventually increase our understanding of the practice and outcomes of SJL in the educational context.